Jack : the true story of Jack & the beanstalk - Shurtliff, Liesl (Alfred A. Knopf, 2015)
Relates the tale of Jack who, after trading his mother's milk cow for magic beans, climbs a beanstalk to seek his missing father in the land of giants.